(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research aims to find out how the use of learning media in non-formal Islamic educational institutions, namely in the Koran education park. Researchers use qualitative methods with a qualitative descriptive approach so that researchers can explain the object under study more clearly and in detail. This research is located in 3 TPAs ​​in Air Tawar Barat Village, North Padang District, Padang City, namely TPA Al-Azhar UNP Mosque, TPA Ikhwanul Muslimin Mosque, and TPA Baitussalam Mosque. The data sources in this research are 18 informants to be interviewed regarding the focus of the problem to be studied. These 18 informants were 1 TPA ​​teacher at the Al-Azhar Mosque UNP, 1 TPA ​​teacher at the Ikhwanul Muslimin Mosque, 1 TPA ​​teacher at the Baitussalam Mosque, 5 students at the TPA at Al-Azhar Mosque UNP, 5 students at the TPA at the Ikhwanul Muslimin Mosque and 5 students. Baitussalam Mosque landfill. Selection of informants using purposive sampling technique and has met the requirements as an informant. The results of the study prove that the use of learning media in TPA Islamic educational institutions in Padang City, to be precise in Air Tawar Barat Village, is fairly good. This is marked by the insights that educators have about media, educators are also able to choose and use media properly. These results were obtained due to factors within the educators themselves and also the support from the leadership of the institution for all the input given by the educators. Although indeed there are still some challenges in the use of media such as the mood of educators when teaching and the physical condition of the students themselves.